2018
DOI: 10.1089/bfm.2017.0183
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Biomarkers of Secretory Activation in Breast Pump-Dependent Mothers of Premature Infants

Abstract: Secretory activation is delayed in mothers who deliver prematurely and is closely tied to CTV, MOM volume, and pumping frequency. MOM biomarkers hold promise as objective research outcome measures and for point-of-care testing to identify and proactively manage mothers at risk for compromised lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…71,[73][74][75] Additionally, MOM synthesis and secretion may also be adversely affected by pregnancy and birth complications and the intense emotional distress associated with having a VLBW infant in the NICU. 73,[76][77][78][79] With recommendations from the American Academy of Pediatrics 80 and quality initiatives focused on MOM, [81][82][83] the initiation rates of MOM provision have increased in many institutions; 81,82 however, disparities in sustaining MOM provision remain. 29,84 Despite high initiation rates and a goal to continue MOM provision after NICU discharge, significantly fewer black VLBW infants continue to receive MOM at NICU discharge compared to non-black infants.…”
Section: Disparities In Breastfeeding Initiation and Durationmentioning
confidence: 99%
“…71,[73][74][75] Additionally, MOM synthesis and secretion may also be adversely affected by pregnancy and birth complications and the intense emotional distress associated with having a VLBW infant in the NICU. 73,[76][77][78][79] With recommendations from the American Academy of Pediatrics 80 and quality initiatives focused on MOM, [81][82][83] the initiation rates of MOM provision have increased in many institutions; 81,82 however, disparities in sustaining MOM provision remain. 29,84 Despite high initiation rates and a goal to continue MOM provision after NICU discharge, significantly fewer black VLBW infants continue to receive MOM at NICU discharge compared to non-black infants.…”
Section: Disparities In Breastfeeding Initiation and Durationmentioning
confidence: 99%
“…Overall actigraphic sensitivity and accuracy are high relative to polysomnography, but specificity is low (Marino et al, 2013). Furthermore, although meta-analysis found the breast fullness survey adequate for determining the timing of lactogenesis II (Perez-Escamilla & Chapman, 2001), using a biomarker such as measuring milk and serum lactose or citrate levels, or weighing breasts (Murase, Wagner, J. Chantry, Dewey & Nommsen-Rivers, 2017; Panwara, Kasem, Wipada, Maysita & Pawin, 2016; Rebecca et al, 2018), would strengthen the approach to determining DLII. Moreover, data available from medical charts on labor length and the timing of first-feeding was sparse and varied by clinician.…”
Section: Limitationsmentioning
confidence: 99%
“…While long labours, caesarean section, and obesity have been associated with delayed SA [ 36 , 37 ] we found no evidence of delayed SA in women delivering by vaginal or caesarean section nor with analgesic administration during caesarean births [ 38 ]. Similarly, Cregan et al found no difference in concentration of milk citrate, lactose, protein, and sodium from mothers of term and preterm infants [ 39 ]. However, there was greater variation in these markers for preterm mothers and milk production was related to how many markers were in the normal range by Day 5 [ 39 ] in that women with fewer markers in the normal range had the lowest milk productions.…”
Section: Secretory Activationmentioning
confidence: 99%
“…Similarly, Cregan et al found no difference in concentration of milk citrate, lactose, protein, and sodium from mothers of term and preterm infants [ 39 ]. However, there was greater variation in these markers for preterm mothers and milk production was related to how many markers were in the normal range by Day 5 [ 39 ] in that women with fewer markers in the normal range had the lowest milk productions. The significance of these data are that previously SA was considered a discrete event with failed SA attributed to either hormonal causes, e.g., no drop in progesterone due to retained placenta, or glandular causes, e.g., insufficient mammary tissue [ 40 ].…”
Section: Secretory Activationmentioning
confidence: 99%